Pengaruh Senam Apiyu Terhadap Kadar Glukosa Darah Pasien Diabetes Mellitus (DM) Tipe II Di Puskesmas Rejosari Kota Pekanbaru - Indah Sri Agustina; Yesi Hasneli N; Erwin Erwin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Diabetes Mellitus (DM) is a disease caused by the body not being able to adequately release or use insulin so that blood glucose levels in the blood are high. The purpose of this study was to determine the effect of APIYU exercise on blood glucose levels of Diabetes Mellitus (DM) Type II patients. Method: Quantitative Research Design Quasy Experiment. The study sample was 34 respondents, Purposive sampling technique which was divided into 2 groups, namely 17 experimental respondents given APIYU exercise intervention and 17 control group respondents were not given APIYU exercise intervention. Both groups continued to take the drugs Glibenclamide and Metformin. The measuring instruments used are observation sheets and glucometers with pre-test and post test for 3 consecutive days after doing APIYU exercise. The statistical tests used are the Paired Samples T Test and the Mann Whitney test. Result:. There was a significant difference in the mean blood glucose levels of the pre-test and post-test in the experimental group with a p value of 0.000. APIYU exercise affects blood glucose levels in Type II Diabetes Mellitus (DM) patients with a ? value of 0.000 (<0.05) Conclusion: APIYU exercise affects the blood glucose level of people with Type II Diabetes Mellitus (DM). These results are expected to be an alternative treatment in controlling blood glucose levels of people with Type II Diabetes Mellitus (DM). Keywords: , ,